2015
DOI: 10.1111/aji.12447
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum TNF-α Levels and Recurrent Spontaneous Miscarriage: A Meta-analysis

Abstract: Most recurrent spontaneous miscarriages (RSMs) are attributed to 'unexplained' factors, the majority of which are immune factors. Furthermore, clinically, only a small number of RSM patients get early diagnosis by testing for antiphospholipid antibodies, whereas most of the patients, present no specific diagnostic indicators. We performed a meta-analysis of observational studies to detect the association between RSM and TNF-α levels. We searched PubMed, EMBase, ScienceDirect, Web of Science, and Chinese databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Also, Ozkan et al (18) detected a significantly high TNF-a/IL-10, TNF-a/ IL-4 and concluded that increased Thl /Th2 cytokine ratios in RPL cases pointed to suppression of antiinflammatory process that might play an important role in the pathogenesis of idiopathic RPL. Recently, Zhang et al (19) found baseline TNF-a levels were higher in patients with recurrent spontaneous abortion than in controls.…”
Section: Discussionmentioning
confidence: 97%
“…Also, Ozkan et al (18) detected a significantly high TNF-a/IL-10, TNF-a/ IL-4 and concluded that increased Thl /Th2 cytokine ratios in RPL cases pointed to suppression of antiinflammatory process that might play an important role in the pathogenesis of idiopathic RPL. Recently, Zhang et al (19) found baseline TNF-a levels were higher in patients with recurrent spontaneous abortion than in controls.…”
Section: Discussionmentioning
confidence: 97%
“…It appears that combining aspirin and heparin has the best results. Patients should start taking heparin as early as possible when pregnant and continue until labor and during puerperium [42][43][44][45][46][47][48][49][50]. Combination of aspirin and heparin is associated with better results.…”
Section: Prednisolone Between 10 and 20 Mg Daily Dosagementioning
confidence: 99%
“…Heparin subcutaneously, for example, low molecular weight heparin one injection per day may prevent recycling of circulating anti-cardiolipins or suppress the secretion of embryotoxic agents or HLA-related agents. It also reduces the percentage of NK (CD56+/CD16+) cells [46][47][48][49][50]. It has been associated with gestational hypertension and diabetes mellitus and mainly with premature labor and low birth weight neonates.…”
Section: Prednisolone Between 10 and 20 Mg Daily Dosagementioning
confidence: 99%
See 2 more Smart Citations